Polycystin-2 Activation by Inositol 1,4,5-Trisphosphate-induced Ca(2+) Release Requires Its Direct Association with the Inositol 1,4,5-Trisphosphate Receptor in a Signaling Microdomain - Sammels, Eva (American Society for Biochemistry and Molecular Biology, 2010)
Autosomal dominant polycystic kidney disease is characterized by the loss-of-function of a signaling complex involving polycystin-1 and polycystin-2 (TRPP2, an ion channel of the TRP superfamily), resulting in a disturbance in intracellular Ca(2+) signaling. Here, we identified the molecular determinants of the interaction between TRPP2 and the inositol 1,4,5-trisphosphate receptor (IP(3)R), an intracellular Ca(2+) channel in the endoplasmic reticulum. Glutathione S-transferase pulldown experiments combined with mutational analysis led to the identification of an acidic cluster in the C-terminal cytoplasmic tail of TRPP2 and a cluster of positively charged residues in the N-terminal ligand-binding domain of the IP(3)R as directly responsible for the interaction. To investigate the functional relevance of TRPP2 in the endoplasmic reticulum, we re-introduced the protein in TRPP2(−/−) mouse renal epithelial cells using an adenoviral expression system. The presence of TRPP2 resulted in an increased agonist-induced intracellular Ca(2+) release in intact cells and IP(3)-induced Ca(2+) release in permeabilized cells. Using pathological mutants of TRPP2, R740X and D509V, and competing peptides, we demonstrated that TRPP2 amplified the Ca(2+) signal by a local Ca(2+)-induced Ca(2+)-release mechanism, which only occurred in the presence of the TRPP2-IP(3)R interaction, and not via altered IP(3)R channel activity. Moreover, our results indicate that this interaction was instrumental in the formation of Ca(2+) microdomains necessary for initiating Ca(2+)-induced Ca(2+) release. The data strongly suggest that defects in this mechanism may account for the altered Ca(2+) signaling associated with pathological TRPP2 mutations and therefore contribute to the development of autosomal dominant polycystic kidney disease.